Attachment Theory: The Mother’s Influences Across The Child’s Lifespan - Abayomi Israel Olaofe; Habibat Princess Odumosu (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
ABSTRACT This study aimed to elucidate the nature of Attachment that exists between mother or caregiver from the lenses of Attachment Theory; explained the tenants of Attachment Theory as it’s relates to Human Development from foetus to adulthood, and the levels and characteristics of attachment existing between mother and/ or caregiver figures. This study discovered that the child diversifies its attachment needs to individuals based on needs and satisfaction of those needs as the child grows from one developmental milestone to another. The study concluded that the child’s Attachment with parents or caregiver is not maintained throughout lifespan, ever it is characterised based on needs.